Eating behaviour of university students in Germany: dietary intake, barriers to healthy eating and changes in eating behaviour since the time of matriculation - Hilger-Kolb, Jennifer; Loerbroks, Adrian; Diehl, Katharina (Appetite, 2017)
A healthy diet plays a key role in preventing obesity and non-communicable diseases such as type 2 diabetes. This is true for all age groups, including young adults. While unhealthy eating habits among young adults, in particular university students, have been identified in former studies, this group has been neglected in existing health promotion strategies. Our aim was to explore baseline dietary intake, common barriers to healthy eating, and changes in eating behaviour among university students since the time of matriculation. We used data from the quantitative part of the Nutrition and Physical Activity Study (NuPhA), a cross-sectional online survey (data collection: 2014/10/31-2015/01/15). Students were recruited from all over Germany. Overall, 689 university students (30.5% male; mean age: 22.69) from more than 40 universities across Germany participated. We found that there is room for improvement with regard to the consumption of specific food groups, for example, fruits and vegetables. The main barriers to healthy eating were lack of time due to studies, lack of healthy meals at the university canteen, and high prices of healthy foods. Cluster analysis revealed that barriers to healthy eating might affect only specific subgroups, for instance freshmen. Changes in eating behaviour since matriculation were found in the consumption of meat, fish, and regular meals. Future qualitative studies may help to explore why university students change their eating behaviour since the time of matriculation. Such knowledge is necessary to inform health promotion strategies in the university setting.